Monoclonal antibodies: applications in non-oncological hematology and transplantation - Carrasco-Yalán, Antonio (2021)
This topic will review the clinical use of monoclonal antibodies in non-cancer hematology, as well as its use in organ and tissue transplantation. Monoclonal antibodies are widely used in hematology either in oncological and nononcological pathologies. Several non-oncological hematologic diseases had been considered “Orphan” with few therapeutic options until the advent of monoclonal antibodies. The area of solid organ and tissue transplantation had grown significantly in quantity and complexity of procedures, including organ and tissue transplantation not completely compatible, hypersensitivity of transfusions and management of transplant rejection. This area had important therapeutic achievements with the use of monoclonal and polyclonal antibodies.